Exploring the Appeal of Lils Beauty Studio: How Brand Exposure and Brand Experience Increase Brand Recall - Saqi, Talila Rosiana Rachma; Yulianti , Ida (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
In order to create a brand that is known to consumers and potential consumers, a brand needs to have a special strategy to raise the brand name to a wide audience. This research aims to analyze the influence of Brand Exposure and Brand Experience on Brand Recall. In this research, quantitative methods were used by collecting data through questionnaires distributed to respondents with a population of all consumers who had received treatment there. Samples were taken using non-probability sampling techniques with 110 respondents. The data obtained was analyzed using IBM SPSS 25.0. The results of research conducted using several series of tests showed that Brand Exposure had a positive and significant influence on Brand Recall. Meanwhile, Brand Experience also shows a positive and significant influence on Brand Recall. These results indicate that the more often consumers are exposed to a brand and the better their experience with that brand, the higher the level of Brand Recall they have. Increasing the frequency of Brand Exposure and creating a positive Brand Experience can be a key strategy for increasing consumer retention of a brand.